A green method to fabricate porous polypropylene fibers: development toward textile products and mechanical evaluation. Issue 5 (March 2020) - Yan, Xiang; Cayla, Aurélie; Salaün, Fabien; Devaux, Eric; Liu, Pengqing; Huang, Tingjian
In this study, a series of immiscible polymer blend fibers with polypropylene (PP) and polyvinyl alcohol (PVA) was obtained by a melt spinning process, and two different draw ratios were attempted. Efforts were made to obtain the porous PP fibers by removing the water-soluble PVA phase. The thermal properties of the blends were tested by thermogravimetric analysis and differential scanning calorimetry. The blends showed excellent thermal stability and differentiated fractionated crystallization behaviors of PP. The melt flow indexes of the blends were evaluated, exhibiting a higher fluidity than that of the neat polymers. Among the possible candidates for the spinning process, only the PP70 –PVA30 had suitable spinnability, for which the draw ratio reached 3. The morphology of the fibers was investigated by selective extraction experiment and scanning electron microscopy, as well as wide-angle X-ray diffraction. The biphasic morphology and the crystallization behaviors varied according to the PVA content. Furthermore, the mechanical properties of the multifilament fibers were studied via tensile testing and dynamical mechanical analysis. The 70/30 weight ratio (PP/PVA) was the most suitable for producing biphasic fibers with a high degree of accessibility in PVA and mechanical properties that increase with the increase in the drawing ratio. The feasibility of fabric knitting was checked, and the mechanical properties and air permeability of the obtained textile structure were also evaluated.